WHY AND HOW EXTENSIVE READING IS APPROPRIATE IN THE CLASSROOM LEARNING? - Murwani Ujihanti (Politeknik Negeri Sriwijaya, 2011)
Extensive reading is the beneficial activity for enhancing life-long learning. It develops language competence by making use of language inputs drawn from extensive reading. Learning skills also increase as it strengthens comprehension, predicting, and analyzing skills. If it is institutionalized policy it will be good practice for increasing learning capabilities, not only learning language. This article presents the reasons why extensive reading is beneficial for boosting learning skills. It also completed by the suggested activities to be implemented in the class-room.